Geophysics for underground engineering - Pavel Bláha; Roman Duras; Jan Gebauer (Acta Polytechnica CTU Proceedings)
The growth of underground engineering brought a need for the use of geophysical methods for research of underground constructions rather different in approach compared to that of civil engineering. These changes relate to surface measurement on the one hand and the development of new specialised methods used for underground work on the other. The results of a complete documentation of mining work, the application of the resistivity methods used underground and also the use of 3D electrical resistivity tomography, are all presented here.